Tax Sanctions as a Moderating Variable of the Influence of E-Filling on Taxpayer Compliance: Penelitian - Bobby Ferly; Rieneke Ryke Kalalo; Loso Judijanto; Agnes Soukotta; Elvina Safitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that inspires previous research and modifies the research being carried out by adding new variations in the form of moderating variables. The data used in this study are primary data that researchers obtained from fifty tax officials and fifty taxpayers spread throughout Indonesia. The data obtained by the researcher was analyzed using the smart LS 4.0 analysis tool. The result in this article show all hypotheses used in this study can be accepted and proven. In the first hypothesis, the E-Filling variable can have a positive relationship direction and a significant influence on the Taxpayer Compliance variable. This is because the P-Values ​​are positive and below the significance level of 0.05, namely 0.008. This means that the implementation of E-Filling can make someone know more precisely how much tax should be paid and immediately decide to pay tax. This, of course, can increase Taxpayer Compliance. In the next hypothesis, the Tax Sanctions variable can also moderate the influence of the e-Filling variable on the Taxpayer Compliance variable because the P-Values ​​are positive and below the significance level of 0.05, namely 0.000, which is more significant than direct testing.